Board Independence, Nomination And Remuneration Committee, And Compensation In Indonesia - Puteri Alfarisa; Iman Harymawan (Jurnal Akuntansi, 2021)
This article aims to examine the relationship between independent commissioners and nomination and remuneration committee (KNR) and their interaction with directors’ compensation using companies listed on the Indonesia Stock Exchange (BEI) and ordinary least square regression analysis technique. This study found that independent commissioners negatively associated with directors' compensation which showed that companies with a higher ratio of independent commissioners provide less directors' compensation due to optimal supervision of management’s opportunistic behavior. In contrast, KNR is positively associated with directors' compensation which means that companies with KNR provide greater compensation because, according to the "optimal contracting approach", the board is assumed to design compensation schemes to provide managers with efficient incentives to maximize shareholder value. Meanwhile, the interaction between the two variables is not associated with directors' compensation because of the negating effect which shows that companies with independent commissioners and KNR do not have a tendency for directors' compensation.